A novel model for the bubble growth in the cavitation region of an injector nozzle. (April 2018) - Liu, Hong; Cai, Chang; Xi, Xi; Yan, Yan'an; Jia, Ming
Highlights: A new model was developed to calculate the bubble growth in the cavitation region. The energy equation is coupled with the thermal boundary layer thickness. The bubble growth is divided into three distinct stages. Liquid pressure plays a significant role on bubble growth. Abstract: A novel thermodynamic model was developed to calculate the bubble growth in the cavitation region of an injector nozzle. The influence of liquid pressure on bubble growth process was evaluated for both homogenous nucleus and heterogeneous nucleus. In this model, the energy equation coupling with the quadratic temperature distribution within the thermal boundary layer was applied with consideration of temporal variation of bubble pressure, radius, velocity and the thickness of the thermal boundary layer. The results show that the evolution of the bubble growth can be divided into three stages, i.e., surface tension controlled stage, transitory stage, and heat transfer controlled stage. The evolution processes of bubble growth from a homogeneous nucleus or a heterogeneous nucleus are much alike other than in the surface tension controlled stage.